Silek Lanyah: A Form of Tourism Performing Art in Padang Panjang City - Syofia, Ninon; Wahyuni, Wahida; Erman, Syaiful (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2024)
This research endeavors to explore the appeal of Silek Lanyah as a form of tourist entertainment in Padang Panjang. Employing a qualitative approach, the study adopts descriptive analysis to elucidate field data and subsequently analyze it in line with the research objectives. Drawing upon the insights of scholars such as Koentjaraningrat on the concept of change, R.M Soedarsono's perspectives on the packaging of tourism art, and I Gusti Ngurah's views on tourist performances, this paper aims to provide a comprehensive understanding of the subject matter. The findings of this investigation underscore the allure of Silek Lanyah as a captivating tourist attraction, capable of enticing visitors to explore and appreciate the charm of Kubu Gadang Tourism Village, while simultaneously showcasing Silek Lanyah as a cherished traditional art form within the region. Through this study, it becomes evident that Silek Lanyah holds significant potential in enriching the cultural landscape of Padang Panjang and contributing to the tourism industry by offering a unique and authentic experience for travelers.